Japan inside out : - Gluck, Jay (Personally Oriented, 1992)
This husband-wife-son team (Jay, Sumi, and Garet Gluck, respectively) have lived for many years in Japan, and their tightly packed volume--revised for the first time since it initially appeared in 1964--provides a plethora of useful and sound advice for the visitor. While most guidebooks attempt an impersonal posture, this one offers refreshingly frank, opinionated, and sometimes passionate personal comments, as well as lively explanations and descriptions of such subjects as sumo, Japanese education, and business practices. The book is organized by region and covers not only where to go but what to do; 2099 local festival dates are given. The prose is choppy; June Kinoshita and Nicholas Palevsky's Gateway to Japan ( LJ 4/15/90) is a more polished guidebook. But the Glucks' work contains so much information (including 135 maps) that it should be almost every library's next selection for an introduction to Japan.